Comparison of Inguinal Hernia Repair Performed under Local and Spinal Anesthesia as A Day-Case Surgery (Journal of Fatima Jinnah Medical University, 2018)
Objectives: The objective of this study is to compare the frequency of inguinal hernia repair performed under local and spinal anesthesia as a day-case surgery.Study Design: Randomized Controlled TrialSetting: Surgical Unit-II, Sir Ganga Ram Hospital, LahoreSubject and Methods: Hundred patients fulfilling the inclusion criteria were selected for study; they were divided into two groups by random number table. In group A hernia repair was done under spinal anesthesia and in group B repair was done under local anesthesia. Spinal anesthesia was given by anesthetist and local anesthesia was given by same team of surgeons. Mesh hernioplasty was performed in all the 100 patients. Patients were discharged when they were pain free {(Visual Analogue Scale (VAS
Keywords: Inguinal hernia, Anesthesia, Day-cases